The role of CBR in the rehabilitation process in home conditions - Samir Bojičić; Bakir Katana; Amila Jaganjac; Amra Mačak Hadžiomerović; Mirsad Muftić; Dinko Remić (Journal of Health Sciences, 2012)
Introduction: Community Based Rehabilitation (CBR) is a strategy within community development for rehabilitation, equalizes opportunities and social integration of incapacitated people. This is a comprehensive strategy of involving people with disabilities in their communities through the development program. CBR system provides for the people with disabilities equal access to treatment and rehabilitation, education, promotes health and healthy living, and also indicates the existence of other features that make these people become full members of society and the community in which they live and is currently used in over 90 countries around the world. Methods: Research was conducted in two CBRs (CBR-Kumrovec and CBR-Saraj Polje) in the department of physical medicine and rehabilitation in the Sarajevo Canton. The study included and statistically treated 97 patients during the period from 01.01.2008 to 31.12.2008 year. Results: In a study from the total number of respondents 65% were women, 35% male respondents, and the most represented were respondents of age group from 71-80 years - 40%. Of all diseases, the most represented were respondents with ICV, 43%. Conclusion: This type of treatment in the home conditions is providing necessary medical rehabilitation services by qualified physical therapists through a sufficiently long period for successful medical rehabilitation in the natural environment of patients (home conditions), and the presence of family members who we can also educate for the enforcement of basic physical procedures and instruct them on the condition of the patient and his perspective.